EFEKTIVITAS PEMBERIAN BUAH PISANG RAJA (MUSA TEXTILIA) TERHADAP PENURUNAN KELELAHAN PADA NELAYAN DI WILAYAH MEDAN BELAWAN - Veronika Manik, Hesti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Work-related fatigue is a common occupational health problem among fishermen due to prolonged working hours, high physical workload, and inadequate rest, which may reduce productivity and increase the risk of work accidents. This study aimed to examine the effectiveness of Musa textilia (king banana) consumption in reducing work fatigue among fishermen in the Medan Belawan area. A quasi-experimental study with a pretest–posttest control group design was conducted involving 60 fishermen, who were divided equally into an intervention group and a control group. The intervention group consumed 300 grams of king banana daily for seven consecutive days, while the control group received no dietary intervention. Work fatigue levels were assessed using the KAUPK2 questionnaire. Data were analyzed using the Wilcoxon signed-rank test. The results demonstrated a statistically significant reduction in work fatigue in the intervention group after banana consumption (p < 0.05), whereas no significant improvement was observed in the control group. These findings indicate that king banana consumption is effective in reducing work-related fatigue among fishermen. Incorporating king bananas as a simple nutritional intervention may serve as a practical strategy to mitigate occupational fatigue in this population.